The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/curroncol30030254
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Volumetric-Modulated Arc Radiation Therapy for Head and Neck Cancer: Evaluation of Benefit on Target Coverage and Sparing of Organs at Risk

Abstract: Background: Radiotherapy is essential in the management of head–neck cancer. During the course of radiotherapy, patients may develop significant anatomical changes. Re-planning with adaptive radiotherapy may ensure adequate dose coverage and sparing of organs at risk. We investigated the consequences of adaptive radiotherapy on head–neck cancer patients treated with volumetric-modulated arc radiation therapy compared to simulated non-adaptive plans: Materials and methods: We included in this retrospective dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…This drop in capacity is due to the need for more resources and personnel to manage the more sophisticated radiotherapy processes while ensuring proper quality [31,32]. The increase in initial treatment sessions and the utilization of adaptive protocols, at least for certain body regions, may also contribute to complexity rise [33]. The dependence of daily treatments on allocated time has two distinct slopes with a breaking point in 2010, which limits the gain in daily capacity from 53.3 to 10.2 patients when adding a work shift (Figure 4c).…”
Section: Discussionmentioning
confidence: 99%
“…This drop in capacity is due to the need for more resources and personnel to manage the more sophisticated radiotherapy processes while ensuring proper quality [31,32]. The increase in initial treatment sessions and the utilization of adaptive protocols, at least for certain body regions, may also contribute to complexity rise [33]. The dependence of daily treatments on allocated time has two distinct slopes with a breaking point in 2010, which limits the gain in daily capacity from 53.3 to 10.2 patients when adding a work shift (Figure 4c).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive radiation therapy is the latest development, which promises to combine high precision therapy and the possibility to reduce treatment margins in the head and neck area. Retrospective studies on offline adaptive radiation therapy (ART offline ) for head and neck cancer showed that re-planning with adaptive radiotherapy may ensure adequate dose coverage and sparing of organs at risk [ 11 13 ]. In a virtual retrospective analysis, Franzese et al simulated the relevance of an adaptive strategy for head–neck cancer patients treated with definitive or post-operative radiotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies on offline adaptive radiation therapy (ART offline ) for head and neck cancer showed that re-planning with adaptive radiotherapy may ensure adequate dose coverage and sparing of organs at risk [ 11 13 ]. In a virtual retrospective analysis, Franzese et al simulated the relevance of an adaptive strategy for head–neck cancer patients treated with definitive or post-operative radiotherapy [ 11 ]. Their results showed that in the absence of re-planning doses to the analyzed organs at risk may increase during the long course of radiotherapy delivered with the VMAT technique with a potential clinical impact in terms of increased toxicity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation